2021
DOI: 10.1093/gerona/glab214
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Characteristics and Hearing Loss in Older Adults: The National Health and Nutrition Examination Survey 2005–2006

Abstract: Background Sleep characteristics might be associated with hearing loss through disturbed energy metabolism and disrupted cochlear blood flow, but prior evidence is limited. This study aims to investigate cross-sectional associations of sleep duration and signs/symptoms of sleep-disordered breathing with hearing in a nationally representative cohort of U.S. older adults aged 70 and over. Methods We studied 632 older adults age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 41 publications
2
36
1
Order By: Relevance
“…However, research on the associations between sleep characteristics and HL is rare. Only three cross-sectional studies have evaluated the associations between sleep disturbance and hearing in adults [23][24][25] ; in a recent analysis, they included 632 older adults (aged >70 years) from the National Health and Nutrition Examination Survey (NHANES) (2005)(2006) and found that >8 hours of sleep was associated with a higher threshold of hearing. 25 The small sample size limited the potential to explore the associations between SPD and HL.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the associations between sleep characteristics and HL is rare. Only three cross-sectional studies have evaluated the associations between sleep disturbance and hearing in adults [23][24][25] ; in a recent analysis, they included 632 older adults (aged >70 years) from the National Health and Nutrition Examination Survey (NHANES) (2005)(2006) and found that >8 hours of sleep was associated with a higher threshold of hearing. 25 The small sample size limited the potential to explore the associations between SPD and HL.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Only three cross-sectional studies have evaluated the associations between sleep disturbance and hearing in adults [23][24][25] ; in a recent analysis, they included 632 older adults (aged >70 years) from the National Health and Nutrition Examination Survey (NHANES) (2005)(2006) and found that >8 hours of sleep was associated with a higher threshold of hearing. 25 The small sample size limited the potential to explore the associations between SPD and HL. Additionally, none of these studies included the Chinese population, nor did they consider the potential impact of factors such as noise.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A casecontrol study using pooled controls in Japan reported that short sleep duration might be a risk factor for idiopathic sudden deafness (Nakamura et al, 2001). The 2005-2006 cycle of the National Health and Nutrition Examination Survey (NHANES) in the United States suggested that longer sleep duration (≥ 8 h per day) was marginally associated with poorer hearing function (Jiang et al, 2021). However, this study was weak in representativeness due to the relatively small sample size of fewer than 1,000 individuals (632 older adults aged 70 years and older).…”
Section: Discussionmentioning
confidence: 99%
“…As for hearing impairment, little is known about its associations with sleep duration. A study of 632 adults aged 70 years or above in the United States reported that longer sleep duration exceeding 8 h was linked with poorer high-frequency hearing (Jiang et al, 2021). Another study of 48,091 adults aged 20-79 years in Japan suggested that individuals with sleep duration exceeding 8 h had a higher risk of hearing loss (Nakajima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of the older population complains of sleep disturbances [161]. A marginal association exists between achieving over eight hours of sleep and impaired highfrequency hearing [162]; however, no evidence of the association between sleep quality and hearing loss has been reported. Nevertheless, several studies have suggested an association between sleep-disordered breathing (SDB) and worse cardiovascular, cognitive, and functional outcomes.…”
Section: Sleepmentioning
confidence: 99%